2015
DOI: 10.1152/ajplung.00270.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial integrity in a neonatal bovine model of right ventricular dysfunction

Abstract: (LV) failure, yet the mechanisms of RV failure are poorly understood. Recent studies suggest cardiac metabolism is altered in RV failure in pulmonary hypertension (PH). Accordingly, we assessed mitochondrial content, dynamics, and function in hearts from neonatal calves exposed to hypobaric hypoxia (HH). This model develops severe PH with concomitant RV hypertrophy, dilation, and dysfunction. After 2 wk of HH, pieces of RV and LV were obtained along with samples from age-matched controls. Comparison with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…[43][44][45][46] In bovine RV compared to LV, Bruns et al reported higher mitochondrial content by DNA copy number and morphometric analysis, as well as increased expression of pro-fusion Mfn1 mRNA, implicating enhanced mitochondrial fusion in the RV. 7,8 Our finding of increased Mfn1 protein expression and increased mtDNA levels in RV compared to LV myocytes similarly support increased mitochondrial fusion and content in RV myocytes, which can potentially underlie their enhanced maximal respiratory capacity. Although we did not directly assess cardiomyocyte ATP production, we observed increased complex V enzyme activity in RV myocytes, in line with the enhanced energetics associated with mitochondrial fusion.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…[43][44][45][46] In bovine RV compared to LV, Bruns et al reported higher mitochondrial content by DNA copy number and morphometric analysis, as well as increased expression of pro-fusion Mfn1 mRNA, implicating enhanced mitochondrial fusion in the RV. 7,8 Our finding of increased Mfn1 protein expression and increased mtDNA levels in RV compared to LV myocytes similarly support increased mitochondrial fusion and content in RV myocytes, which can potentially underlie their enhanced maximal respiratory capacity. Although we did not directly assess cardiomyocyte ATP production, we observed increased complex V enzyme activity in RV myocytes, in line with the enhanced energetics associated with mitochondrial fusion.…”
Section: Discussionsupporting
confidence: 60%
“…29 Bruns et al showed in control calves increased RV versus LV mitochondrial content and expression of COXI (mitochondrial complex IV) and Mfn1, which regulates mitochondrial fusion. 7,8 Taken together, these studies suggest a mitochondrial basis for ventricular differences in metabolism.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, all differences noted in the RV were also observed in the LV, suggesting an overall response to hypoxia rather than chamber-specific adaptation. A small shift in metabolism consistent with an early switch to glycolytic metabolism was also noted, although again this was observed in both ventricles (30), suggesting that at this early stage of PH where RV function is largely compensated, mitochondrial and metabolic pathways do not contribute to the response to pressure overload.…”
Section: Pathways and Targetsmentioning
confidence: 80%
“…Consistent with previous work demonstrating metabolic dysregulation in the left ventricle (LV) during heart failure (19,204,215), it was speculated that similar mitochondrial and metabolic abnormalities might be present in the RV. Surprisingly, following 2 wk of hypoxic exposure, mitochondrial function appeared to be largely maintained, with no significant changes in mitochondrial structure or dynamics and only small reductions in mitochondrial number and complex I activity (30). Interestingly, all differences noted in the RV were also observed in the LV, suggesting an overall response to hypoxia rather than chamber-specific adaptation.…”
Section: Pathways and Targetsmentioning
confidence: 92%